Levantamento preliminar dos dados de recursos hídricos do município de Ourilândia do Norte - Pará, Brasil - SILVA, Wagner Fernando da Veiga e (2019)
The hydraulic potential of the largest river basin of the world, located in the Amazon region, has attracted worldwide interest. Taking in account the decrease of fresh water reserves around the planet, the waters of Amazon Rivers have attained important commercial and strategic values. The goal of this work was to identify the agent responsible for the degradation of fresh water resources in the municipality of Ourilândia do Norte, in order to get information for the preservation and conservation of water resources. Since its creation, Ourilândia do Norte has been affected by transformation and degradation of its fresh water sources, because of non-sustainable activities such as unlawful quarries, logging, pollution, lack of basic sanitation, among others. The current situation is critic: there is no basic sanitation, there is shortage of fresh water and sewage, the small rivers are being polluted and the flooded forest is being occupied with no planning. On the basis of our survey, it is proposed a model for the management of river basins which’s goal is to pay attention to the physiographic, social, environmental and economic characteristics of Ourilândia do Norte.